Effect of Hydropriming on Field Emergence, Crop Performance and Seed Yield of Maize Parental Lines during Winter and Spring-Summer Season - SUDIPTA BASU; S.P. SHARMA; M. DADLANI (Seed Research, 2026)
Seeds of parental lines viz. CM 202, CM111, CM500 and CM501 of maize were subjected to pre-sowing hydropriming and its efficacy was evaluated on their field emergence, vegetative growth, flowering and seed yield during winter and spring summer seasons. Hydropriming treatments (12 h at 25°C and 48 h at 10°C, followed by 12 h at 25°C) significantly improved the field emergence, its rate, uniformity and early seedling growth but had no effect on vegetative growth, flowering behaviour and seed yield of the parental lines in both the seasons. The beneficial effects of hydropriming were less pronounced in spring summer than winter season due to prevalent sub-optimum temperatures in spring summer. Among hydration treatments, 24 h at 25°C was found to be more promising than 48 h at 10°C followed by 12 h at 25°C. The study highlighted the potential of hydropriming treatments in improving field emergence and early seedling growth during winter and spring-summer seasons.